CORAK PENAFSIRAN ISYARI DALAM TAFSIR JEMA'AT AHMADIYAH QADIYAN (Satu Analisa dalam Perspektif Ilmu Tafsir) - Andi Putra Ishak (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
Ahmadiyah Qadiyan interpretation controversy has caused tremendous reaction from Muslims around the world, not only in his native land claimed as the Ahmadis non-Muslim minority, even in the Islamic world is considered heretical groups in and out of Islam. This fallacy stems from religious interpretations that do not comply with the disciplines of Islam, giving rise to different views in terms of religious principles. However, Ahmadiyah still claiming to be performer true religion of Islam, because in principle they still cling to the Qur'an and other Islamic scientific sources such as tradition, the views of prophet Muhammad companions and his followers. In addition they also have their own interpretation book is